# Thread: How to show this sequence converges?

1. ## How to show this sequence converges?

Show that
$\displaystyle a_n=(\sum_{k=1}^\infty \frac{1}{k})-log(n+1)$ converges to some real number.

The problem hints that I'm supposed to use the fact that
$\displaystyle \sum_{k=1}^\infty \frac{x}{k(x+k)}$ converges uniformly on [0,1], which I've already proved.

I can't figure out how to connect these two facts at all... any help?

2. Originally Posted by paupsers
Show that
$\displaystyle a_n=(\sum_{k=1}^\infty \frac{1}{k})-log(n+1)$ converges to some real number.

The problem hints that I'm supposed to use the fact that
$\displaystyle \sum_{k=1}^\infty \frac{x}{k(x+k)}$ converges uniformly on [0,1], which I've already proved.

I can't figure out how to connect these two facts at all... any help?

My opinion :

Can we use that

$\displaystyle \frac{1}{k} > \ln(1 + \frac{1}{k}) > \frac{1}{k+1}$ ?

then the series $\displaystyle \left( \sum_{k=1}^n \frac{1}{k} \right ) - \ln(n+1)$

$\displaystyle = \left( \sum_{k=1}^n \frac{1}{k} \right ) - \sum_{k=1}^n \ln( 1 + \frac{1}{k} )$

$\displaystyle = \sum_{k=1}^n \left( \frac{1}{k} - \ln( 1 + \frac{1}{k} ) \right) < \sum_{k=1}^n \left( \frac{1}{k} - \frac{1}{k+1} \right)$ $\displaystyle = \sum_{k=1}^n \frac{1}{k(k+1)}$ which is convergent .

Also , since $\displaystyle \frac{1}{k} > \ln(1 + \frac{1}{k} )$ , the series is greater than zero , it is bounded .

I think there may be some errors but anyway , you can take a look and perhaps it can help you a little .

3. Originally Posted by paupsers
Show that
$\displaystyle a_n=(\sum_{k=1}^\infty \frac{1}{k})-log(n+1)$ converges to some real number.

The problem hints that I'm supposed to use the fact that
$\displaystyle \sum_{k=1}^\infty \frac{x}{k(x+k)}$ converges uniformly on [0,1], which I've already proved.

I can't figure out how to connect these two facts at all... any help?

Because of the uniform convergence, the sum $\displaystyle f(x)=\sum_{k=1}^\infty \frac{x}{k(x+k)}$ is continuous on $\displaystyle [0,1]$. Furthermore, you may integrate term by term on $\displaystyle [0,1]$. Note also that $\displaystyle \frac{x}{k(x+k)}=\frac{1}{k}-\frac{1}{x+k}$. We get:

$\displaystyle \sum_{k=1}^\infty \left(\frac{1}{k}-(\log(k+1)-\log k)\right)=\int_0^1 f(x) dx$.

The important thing is that the right-hand side is finite.

The above shows (means) that $\displaystyle \sum_{k=1}^n \left(\frac{1}{k}-(\log(k+1)-\log k)\right)$ has a finite limit as $\displaystyle n\to\infty$.

However, this partial sum can be rewritten as $\displaystyle \left(\sum_{k=1}^n \frac{1}{k}\right)-\log (n+1)$...

4. Originally Posted by Laurent
We get:

$\displaystyle \sum_{k=1}^\infty \left(\frac{1}{k}-(\log(k+1)-\log k)\right)=\int_0^1 f(x) dx$.
I don't understand how you got to this point. What exactly did you integrate?

5. Originally Posted by paupsers
I don't understand how you got to this point. What exactly did you integrate?
$\displaystyle f$ between 0 and 1...

$\displaystyle \int_0^1 f(x)dx = \int_0^1 \left(\sum_{k=1}^\infty \frac{x}{k(x+k)}\right)dx$ $\displaystyle =\sum_{k=1}^\infty \int_0^1 \frac{x}{k(x+k)}dx$,

(last step justified by uniform convergence) and used the expression I gave to simplify the computation of the last integral.